2020
DOI: 10.1177/1359105320951620
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the prevalence of anxiety symptoms during coronavirus epidemics

Abstract: Coronavirus pandemics causes systemic and mainly pulmonary changes. We assessed the prevalence of generalized anxiety disorder (GAD) in pandemic survivors and the general population. Papers indexed by MEDLINE/PubMed, The Cochrane, Embase, Lilacs, Scielo, Psycoinfo, and Pepsic databases were searched to April 2020, using GAD and Coronavirus (CoV) infection as keywords. Sixteen studies with 25,779 participants in eight countries were included. A 46% pooled prevalence of anxiety symptoms (95% CI 33.9–58.2%) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 37 publications
7
56
0
4
Order By: Relevance
“…A large number of studies support that the conclusion that the novel coronavirus (SARS-CoV-2) and its corresponding disease (COVID- 19) have dramatically impacted people's mental health and behavior [1][2][3][4][5], with very few studies suggesting otherwise [6]. Mental health hotlines in the United States experienced 1,000% increases during the month of April, when most people were under lockdown because of the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies support that the conclusion that the novel coronavirus (SARS-CoV-2) and its corresponding disease (COVID- 19) have dramatically impacted people's mental health and behavior [1][2][3][4][5], with very few studies suggesting otherwise [6]. Mental health hotlines in the United States experienced 1,000% increases during the month of April, when most people were under lockdown because of the pandemic [7].…”
Section: Introductionmentioning
confidence: 99%
“…This country continues to witness the highest incidence and mortality rates among Global North countries [26]. Such high rates aggravate the psychological impacts of the disease on infected and non-infected individuals [1].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has presented unexpected and significant stressors that have been demonstrated to negatively impact mental health worldwide [10,12]. While for some individuals, the mental health impacts are considerable, including posttraumatic stress disorder, self-harm, and suicidal ideation [20,41], most people will experience mild to moderate symptoms of stress, anxiety, and low mood [11,42,43]. Such subclinical symptoms have been shown to be particularly responsive to self-directed mental health interventions, including virtual resources [44].…”
Section: Principal Findingsmentioning
confidence: 99%
“…In the United States the COVID-19 Impact Survey found that 34.4% of households with children ≤ 12 years old were food insecure in April 2020, compared with 15.1% in 2018 (7) . Further, multiple studies have found that the COVID-19 pandemic and lockdowns have negatively affected mental health in diverse contexts and populations (8,9) . Nevertheless, evidence on food insecurity and mental health in LMICs, particularly in Latin America, that compares rates before and during the pandemic are limited.…”
Section: Introductionmentioning
confidence: 99%